2006
DOI: 10.1158/0008-5472.can-06-1497
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adenoma Progression to Adenocarcinoma in a 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone–Induced Lung Tumorigenesis Model in A/J Mice by Tea Polyphenols and Caffeine

Abstract: The present study investigated the inhibitory effects of Polyphenon E [a standardized green tea polyphenol preparation containing 65% (À)-epigallocatechin-3-gallate] and caffeine on 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung tumor progression from adenoma to adenocarcinoma. Female A/J mice were treated with a single dose of NNK (103 mg/kg body weight, i.p.) and kept for 20 weeks for the mice to develop lung adenomas. The mice were then given a solution of 0.5% Polyphenon E or 0.044% caff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 36 publications
10
133
1
Order By: Relevance
“…A linkage between the level of phosphorylated JNK and the sensitivity to TxA 2 has been previously reported in cells of other tumor types (Miggin and Kinsella, 2001;Li et al, 2007), whereas studies in lung cancer cells have found no correlation . The data on the response of p38 phosphorylation to NNK in cancer studies are limited, whereas it has been well established that NNK can stimulate JNK activation in lung cancer of animal models (Kim et al, 2006;Lu et al, 2006). In this study, the phosphorylated p38 was shown to be influenced only by TxA 2 , whereas activation of JNK was demonstrated to be stimulated merely by NNK.…”
Section: Discussionmentioning
confidence: 55%
“…A linkage between the level of phosphorylated JNK and the sensitivity to TxA 2 has been previously reported in cells of other tumor types (Miggin and Kinsella, 2001;Li et al, 2007), whereas studies in lung cancer cells have found no correlation . The data on the response of p38 phosphorylation to NNK in cancer studies are limited, whereas it has been well established that NNK can stimulate JNK activation in lung cancer of animal models (Kim et al, 2006;Lu et al, 2006). In this study, the phosphorylated p38 was shown to be influenced only by TxA 2 , whereas activation of JNK was demonstrated to be stimulated merely by NNK.…”
Section: Discussionmentioning
confidence: 55%
“…In our recent study, the oral administration of 0.5% Polyphenon E (PPE, a standardized green tea polyphenol preparation containing 65% EGCG, 25% other catechins, and 0.6% caffeine) or 0.044% caffeine in the drinking fluid for 32 weeks was found to inhibit the progression of lung adenomas to adenocarcinomas in A/J mice that had been treated with a single dose of NNK 20 weeks earlier [17]. Immunohistochemical (IHC) analysis showed that PPE and caffeine treatment inhibited cell proliferation in adenocarcinomas, enhanced apoptosis in adenocarcinomas and adenomas, and decreased levels of c-Jun and phospho-Erk1/2.…”
Section: Lung Tumorigenesismentioning
confidence: 99%
“…Administration of green tea, black tea, EGCG, or theaflavins during initiation or promotion stages was shown to significantly decrease (4-methylnitrosamino)-1-(3-pyridyl)-1-butanon (NNK)-induced lung tumorigenesis in rats, mice, or hamsters [9][10][11][12][13][14][15][16][17]. Treatment with green or black tea for 60 weeks also inhibited the spontaneous formation of lung tumors in A/J mice [18].…”
Section: Lung Tumorigenesismentioning
confidence: 99%
“…Caffeine has also been reported to induce p53-independent G 1 -phase arrest in lung adenocarcinoma cell lines (Qi et al, 2002). Additionally, caffeine has been shown to inhibit epidermal growth factor (EGF)-induced cell transformation in the JB6 mouse epidermal cell line (Nomura et al, 2005), inhibit the progression of lung adenoma to adenocarcinoma (Lu et al, 2006), and suppress metastasis in a transgenic mouse model of mammary tumors .…”
Section: Introductionmentioning
confidence: 99%